2019
DOI: 10.3390/nano9101435
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Hydroxyapatite on Graphene Supports for Biomedical Applications: A Review

Abstract: Hydroxyapatite (HA) has been widely used in fields of materials science, tissue engineering, biomedicine, energy and environmental science, and analytical science due to its simple preparation, low-cost, and high biocompatibility. To overcome the weak mechanical properties of pure HA, various reinforcing materials were incorporated with HA to form high-performance composite materials. Due to the unique structural, biological, electrical, mechanical, thermal, and optical properties, graphene has exhibited great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 98 publications
(144 reference statements)
1
29
0
Order By: Relevance
“…Partly, the incorporation of β-TCP has increased the mechanical properties, which could induce an improved mechanotransduction effect to regulate cells differentiation. Actually, our results are in accordance with previous studies, which indicate that novel GO-CaP nanocomposites could synthetically promote osteogenesis of MSCs and further enhance calcium deposition by osteoblasts [72,73]. As discussed above, the simultaneous incorporation of β-TCP and GO nanoparticles facilitates biomineralization, and subsequentially provides a biomimetic environment for BMSC osteogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Partly, the incorporation of β-TCP has increased the mechanical properties, which could induce an improved mechanotransduction effect to regulate cells differentiation. Actually, our results are in accordance with previous studies, which indicate that novel GO-CaP nanocomposites could synthetically promote osteogenesis of MSCs and further enhance calcium deposition by osteoblasts [72,73]. As discussed above, the simultaneous incorporation of β-TCP and GO nanoparticles facilitates biomineralization, and subsequentially provides a biomimetic environment for BMSC osteogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…The properties of scaffolds mainly depend on the nature of the biomaterial. Therefore, biomaterial selection is critical in tissue engineering (28).Hydroxyapatite has been widely used for bone repair, attribute to their simple preparation, low-cost, and the chemical likeness of calcium phosphates to bone mineral (29,30).Compared with 2D plates, 3Dscaffolds offer a porous structure for cell growth and attachment, thus enhancing mechanical connection between the implanted biomaterial and surrounding bone tissue (28). Pu et al reported that the unique structure of the bilayer scaffolds promotes collagen ber deposition, cell proliferation, and ingrowth of smooth muscle cells and endothelial cells in vivo (31).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the gels reported in this study incorporated hydroxyapatite particles (20 mg mL À1 ), which have been proven to increase cell attachment and lead to osteogenic differentiation from osteogenic progenitor cells. 67,68 The hydroxyapatite particles were mixed homogeneously with the bioink-cell mixture during the manufacturing process. This enabled a good cell-particle interaction; moreover, the presence of hydroxyapatite further increased the viability and proliferation of the pre-osteoblast cells.…”
Section: Mesenchymal Stem Cells Bone and Cartilage Scaffoldsmentioning
confidence: 99%